KAJIAN KERAGAAN PETANI KOPI SOLOK RADJO DI KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Cindy Paloma; Rini Hakimi; Vonny Indah Mutiara; Helmi Helmi (Agros Journal of Agriculture Science, 2023)
Coffee is a crop with great potential to be developed because it has an international market share. Lembah Gumanti District is one of the coffee-producing areas in Solok Regency, where the Solok Radjo Cooperative fosters it. This study aims to determine the characteristics of coffee farmers and the performance of coffee farming in the Lembah Gumanti sub-district. The research used a survey method and collected samples of 70 farmers by purposive sampling. The results showed that most of the farmers (41 percent) were in the elderly range of 51-60 years, had a low level of education, their main livelihood was in the agricultural sector, and had more than 20 years of farming experience. Demonstrations of coffee farming include planting patterns on the edge of the land, in between horticultural crops such as chilies, potatoes, cabbage ,and onions, as Welland coffee in monoculture. The age of coffee plants ranges from 3-5 years, which at this age h has not experienced maximum production at this ages; the existence of the Solok Radjo cooperation is in the moderate category, in which farmers get seeds, fertilizer, and a place to market coffee production, but have yet reached the benefits of guaranteeing coffee price stability. For the development of coffee in the Lembah Gumanti District, farmers hope that there will be a guarantee for a more stable coffee selling price so that the income contribution from the coffee plant increases.Kopi merupakan tanaman yang sangat potensial untuk dikembangkan, karena memiliki pangsa pasar internasional. Kecamatan Lembah Gumanti merupakan salah satu daerah penghasil kopi di Kabupaten solok, dimana dibina oleh Koperasi Solok Radjo. Penelitian ini bertujuan untuk mengetahui karakteristik petani kopi dan keragaaan usahatani kopi di kecamatan Lembah Gumanti. Metode penelitian menggunakan metode survei dan pengambilan sampel 70 petani secara purposive sampling. Hasil penelitian menunjukkan bahwa sebagian besar petani (41 persen) berada di rentang usia lanjut 51-60 tahun, tingkat pendidikan rendah, mata pencarian utama di sektor pertanian dan sudah memiliki pengalaman usahatani lebih dari 20 tahun. Keragaan usahatani kopi diantaranya melakukan pola penanaman di pinggir lahan, di sela dengan tanaman hortikultura seperti cabe, kentang, kol dan bawang, serta penanaman kopi secara monokultur. Umur tanaman kopi berkisar antara 3-5 tahun, yang mana pada umur ini belum mengalami produksi maksimal. Manfaat keberadaan koperasi Solok Radjo berada pada kategori sedang, yang mana petani mendapatkan bibit, pupuk dan tempat memasarkan hasil produksi kopi, namun belum sampai pada manfaat penjaminan kestabilan harga kopi. Untuk pengembangan kopi di Kecamatan Lembah Gumanti petani berharap terdapat jaminan harga jual kopi yang lebih stabil agar kontribusi pendapatan dari tanaman kopi meningkat.